2020
DOI: 10.1002/jeab.635
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcer pathology II: Reward magnitude, reward delay, and demand for alcohol collectively relate to college students' alcohol related problems

Abstract: The reinforcer pathologies model of addiction posits that two characteristic patterns of operant behavior characterize addiction. Specifically, individuals suffering from addiction have elevated levels of behavioral economic demand for their substances of abuse and have an elevated tendency to devalue delayed rewards (reflected in high delay discounting rates). Prior research has demonstrated that these behavioral economic markers are significant predictors of many of college students' alcohol‐related problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Consistent with the reinforcer pathologies model (Bickel & Athamneh, 2020; Bickel et al, 2020; Bickel et al, 2012; Bickel et al, 2011; Bickel et al, 2014; Jarmolowicz, Reed, DiGennaro Reed, et al, 2016), the interaction between behavioral economic demand and delay discounting rates was the most robust predictor of medication decision making. This specificity is notable given that most iterations of the reinforcer pathologies model (Bickel et al, 2011; Lemley et al, 2016; Reed, 2015; Stancato et al, 2020) omit probability discounting as a component (cf. Jarmolowicz, Reed, DiGennaro Reed, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the reinforcer pathologies model (Bickel & Athamneh, 2020; Bickel et al, 2020; Bickel et al, 2012; Bickel et al, 2011; Bickel et al, 2014; Jarmolowicz, Reed, DiGennaro Reed, et al, 2016), the interaction between behavioral economic demand and delay discounting rates was the most robust predictor of medication decision making. This specificity is notable given that most iterations of the reinforcer pathologies model (Bickel et al, 2011; Lemley et al, 2016; Reed, 2015; Stancato et al, 2020) omit probability discounting as a component (cf. Jarmolowicz, Reed, DiGennaro Reed, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These developments have yielded actionable insights into the processes that drive negative health decision making in substance use disorder and obesity (Amlung et al, 2016;Epstein et al, 2010;Stein et al, 2017). Inductively, these findings have served as the foundation for theoretical models describing these conditions, such as the reinforcer pathologies model (Bickel et al, 2011(Bickel et al, , 2016Jarmolowicz, Reed, DiGennaro Reed, et al, 2016;Lemley et al, 2016;Reed, 2015;Stancato et al, 2020). Such models describe how behavioral economic processes-delay discounting, behavioral economic demand, and (to a lesser extent) probability discounting-interactively relate to clinical disorders, both in isolation and in the transdiagnostic features shared between them.…”
mentioning
confidence: 99%
“…These domains are commonly known as excessive substance demand and steep delayed‐reinforcer discounting, respectively. Support for the reinforcer pathology model of addiction has come from human laboratory studies showing an interaction between excessive demand and steep discounting in people who use addictive substances (e.g., McIntyre‐Wood et al, 2021; Naudé et al, 2021; Stancato et al, 2020; Weidberg et al, 2019), although other studies have found nonsignificant interactions (e.g., Acuff et al, 2018; Aston et al, 2016). Behavioral economics research has also led to the development of novel interventions for substance use and addictive behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic alcohol use may also be linked to low loss aversion ( Bernhardt et al, 2017 ), possibly independent of strong delay discounting ( Thrailkill et al, 2022 ). Conflicting reports on delay discounting and loss aversion have appeared, especially concerning non-dependent drinking ( Campbell et al, 2021 ; Herman and Duka, 2020 ; Mayhew et al, 2020 ; Poulton et al, 2022 ; Stancato et al, 2020 ; Tucker et al, 2021 ; Zorick et al, 2022 ). Delay discounting cannot reliably distinguish between different levels, patterns, or problems of non-dependent drinking ( Campbell et al, 2021 ; Herman and Duka, 2020 ; Mayhew et al, 2020 ; Poulton et al, 2022 ; Stancato et al, 2020 ; Tucker et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting reports on delay discounting and loss aversion have appeared, especially concerning non-dependent drinking ( Campbell et al, 2021 ; Herman and Duka, 2020 ; Mayhew et al, 2020 ; Poulton et al, 2022 ; Stancato et al, 2020 ; Tucker et al, 2021 ; Zorick et al, 2022 ). Delay discounting cannot reliably distinguish between different levels, patterns, or problems of non-dependent drinking ( Campbell et al, 2021 ; Herman and Duka, 2020 ; Mayhew et al, 2020 ; Poulton et al, 2022 ; Stancato et al, 2020 ; Tucker et al, 2021 ). Similarly, the scarce research on probability discounting indicates that risk-seeking for gains and risk aversion for losses are associated with moderate to severe Alcohol Use Disorder but possibly not with less problematic drinking ( Bernhardt et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%